INTEGRASI KONSEP DAN APLIKASI DALAM MENENTUKAN PERILAKU KONSUMSI DALAM KEGIATAN EKONOMI MUSLIM - Dewi Fatmala Putri; Syakur, Ahmad (Pusat Riset dan Inovasi Nasional, 2023)
In Muslim economic activities, consumption behavior should be aligned with the principles of Islamic economics, which include justice, balance, and blessings. Excessive and unnecessary consumption should be avoided as it can harm oneself and others. Islam teaches its followers not to harm themselves in this world and the hereafter by engaging in excessive behavior to fulfill their needs and worldly pursuits. This research adopts a qualitative approach by conducting a literature review and content analysis to identify key concepts in Islamic economics relevant to Muslim consumption behavior in economic activities. A good integration between the concepts and applications of Islamic economics in the context of consumer behavior can shape ethical, responsible, and sustainable consumption behavior. These concepts guide the choice of halal products and promote a balance between the needs and desires of individual Muslims. Furthermore, the implementation of these concepts in daily consumption practices can help Muslim individuals avoid excessive consumption, minimize wastefulness, and enhance social benefits in economic activities.